Model for Estimating PM2.5 Concentration Using Aerosol Optical Depth Data in the Muang District of Chiang Mai Province - Buakhao, Laddawan (YRU Journal of Science and Technology, 2023)
The level of fine particulate matter (PM2.5) has been above the average for several months, which has caused air pollution issues in Chiang Mai. The objective of this research was to examine PM2.5 values by developing a mathematical model that utilized optical depth data from ground-based measurement devices and by analyzing the annual trend of PM2.5 values. Two locations were investigated and showed that (1) Chiang Mai Government Center Station was found to have an R2 of 0.76, RMSE of 9.93 micrograms per cubic meter, and MBE of -0.25 micrograms per cubic meter, and (2) Yupparaj Wittayalai School Station had an R2 of 0.81, RMSE of 9.44 micrograms per cubic meter, and MBE of 0.20 micrograms per cubic meter. The model was built to ensure that its output is compatible with measurement data that can be utilized in actual computations, which is useful for giving warnings and performing pollution prevention actions. In terms of the annual cycle of PM2.5, it was discovered that the value climbed from December to April, with its highest level in March, then gradually declined from May to November due to the rainy season. During the rainy season, there is a reduction in the levels of PM2.5 because of rainwater washing away some of the particles.